1981
DOI: 10.1002/j.1538-7305.1981.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource Sharing for Efficiency in Traffic Systems

Abstract: Experience has shown that efficiency usually increases when sep arate traffic systems are combined into a single system. For example, if Group A contains 10 trunks and Group Β 8 trunks, there should be fewer blocked calls if A and Β are combined into a single group of 18 trunks. It is intuitively clear that the separate systems are less efficient because a call can be blocked in one when trunks are idle in the other. Teletraffic engineers and queuing theorists widely accept such efficiency principles and often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 17 publications
(10 reference statements)
2
98
0
Order By: Relevance
“…Our models provide a new simple framework that helps in assessing the effects on pooling of utilization, variability, and service design. While this is not aimed as a review paper, our framework also relates, as it happens, rather disparate concepts and results, for example (Bramson 1994, Jackson 1957, Klimov 1974, Neuts 1981, Smith and Whitt 1981, and Tcha and Pliska 1977. We believe that the usefulness of the framework goes beyond the original motivating applications, pertaining to the design of telephone call centers (Brigandi et al 1994 (Burbidge 1991), team-based product development (Adler 1995), business reengineering (Buzacott 1996, Hammer 1990, Hammer and Champy 1993, and Loch 1998) (elaborated on below), and more.…”
Section: Motivationmentioning
confidence: 99%
“…Our models provide a new simple framework that helps in assessing the effects on pooling of utilization, variability, and service design. While this is not aimed as a review paper, our framework also relates, as it happens, rather disparate concepts and results, for example (Bramson 1994, Jackson 1957, Klimov 1974, Neuts 1981, Smith and Whitt 1981, and Tcha and Pliska 1977. We believe that the usefulness of the framework goes beyond the original motivating applications, pertaining to the design of telephone call centers (Brigandi et al 1994 (Burbidge 1991), team-based product development (Adler 1995), business reengineering (Buzacott 1996, Hammer 1990, Hammer and Champy 1993, and Loch 1998) (elaborated on below), and more.…”
Section: Motivationmentioning
confidence: 99%
“…. The Erlang-B formula plays an important role in many problems of teletraffic theory and this is probably the reason why it has been the subject of intensive study, as shown in references [17] [18] [19] [20] [26]. In several teletraffic studies the need arose to extend the definition of Erlang-B function to non-integer values of x by using its analytical extension, ascribed to R. Fortet [27, pag.…”
Section: Assumptionsmentioning
confidence: 99%
“…The property f 1 ≥ α B(α, κ) may be established as a direct consequence of the convexity of the Erlang-B function (see [26]). …”
Section: The Efficiency Objective Function Lemmamentioning
confidence: 99%
“…The basic pooling models on which this work is based on is described in Kleinrock (1976 pp.272-290). Smith and Whitt (1981) and Benjaafar (1995) showed that a pooled system is better than a dedicated one if arrivals and service times have the same distribution. Buzacott (1996) considered a serial system with n stages where each customer is served by a distinct server at each stage, and transformed this system into a parallel system with n servers in which each server can perform the operations required for all n stages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From Equation (7), the average system delay is given by: Smith and Whitt (1981) showed that when service rates are different, pooling can be counterproductive. By considering an example where two M/M/1 queues are pooled, they demonstrate that the average waiting time can be arbitrarily large if the two service rates differ greatly from each other.…”
Section: Effect Of Service Timementioning
confidence: 99%